Accurate optical measurement of surface acoustic wave phase velocity - Weigel, Robert; Holm, Andreas; Russer, Peter; Ruile, Werner; Soelkner, Gerald (IEEE Ultrasonics Symposium, 1993)
A high-resolution technique for the optical detection of the phase and amplitude of high frequency surface acoustic waves (SAW's) is presented. The test setup incorporates a mode-locked picosecond laser, harmonic mixing, and coherent detection, and it allows not only the measurement of the surface wave field but also the direct determination of the phase velocity. A measurement bandwidth in excess of 2 GHz is achieved. The maximum scan length was 4 cm. As a substrate, LiNbO3 has been used for the test measurements. Minimum detectable surface displacement and dynamic range were 1 pm/Hz1/2 and 40 dB, respectively. The method enables the determination of the phase velocity with a resolution of 1.5·10-5 in dependence of crystal cut, temperature and frequency
elib2cris::1512001600,weigel1993l